Pemberdayaan Masyarakat Melalui Pelatihan Dasar Pemandu Wisata Lokal Di Dusun Mendiro Desa Panglungan - Kartika, Dhian Satria Yudha; Endriana, Fathika; Halila, Azaria Ainun; Pratama, Virgiawan Yoga; Rengganis, Aidha Kiftia (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Community empowerment aims to increase the ability and skills independently to develop and innovate, through basic local tour guide training activities as a community empowerment program that will help the people in Dusun Mendiro know the basics of tour guides which will later be used to improve the economy of the surrounding community. However, the basic training for local tour guides held by KKN students from the East Java "Veteran" National Development University invited academics from the tourism sector to become speakers in this training. Apart from that, there is also assistance from the Forestry Service Branch of the Nganjuk Working Area. From this training activity, it was concluded that the local tour guides in Mendiro Hamlet still lack a sense of trust when communicating and lack detailed knowledge about existing attractions. So that the interpretation and intonation skills possessed by local tour guides in Mendiro Hamlet still need to be considered and trained independently, through the basic material presented it is hoped that this will become a provision for preparation for local tour guides when guiding tourists. This study uses 3 stages, namely planning, implementation, and evaluation. With a qualitative approach, it helps researchers find results that are in accordance with the conditions that occur in the field.